The relationship between genes associated with the pain pathways and the development of chronic shoulder pain and disability in South African breast cancer survivors - Firfirey, Firzana (Department of Human Biology, 2025)
Background A growing challenge in South Africa (SA) healthcare is the frequency of chronic shoulder pain and disability among breast cancer survivors (BCS). Compounding this issue is that a significant number of BCS in South Africa are low-income individuals, exacerbating the economic burden associated with managing chronic pain and disability. These sequelae can last for as much as 6 years post-surgery and thereby negatively impact the overall quality of life. The current standard treatment in SA for acute and chronic pain include opioids and opioid derivatives. Several risk factors have been highlighted to increase susceptibility to developing the sequelae which include severe acute post-operative pain and genetics. Polymorphisms within genes functioning within the opioid signalling and pain pathways have been implicated in variability in opioid use and the development of chronic musculoskeletal pain and disability conditions. The SA population has a diverse genetic background and an increasing BCS cohort that are of mixed ancestry. This thesis therefore sought to identify potential genetic contributors to variability in pain response and to understand the development of chronic pain and disability in SA BCS of mixed ancestry background. The study aimed to (i) assess chronic shoulder pain and disability symptoms using self reported outcome measures in a unique SA BCS cohort; (ii) investigate non-genetic and genetic risk factors associated with chronic pain and disability; (iii) explore the genetic variability in key genes within the opioid signalling and pain pathways and (iv) characterise the potential biological and functional networks related to the opioid signalling and pain pathways. The objectives included : i. Describing the prevalence of chronic pain and disability in BCS using the Shoulder Pain and Disability Index (SPADI) in the SA cohort of mixed ancestry ii. Examine the genetic association between eight prioritised single nucleotide polymorphisms in three candidate genes: (I) ATP-Binding Cassette- Subfamily B, Member 1 Gene (ABCB1); (rs1045642 G>A; rs1128503 G>A), (II) Opioid Receptor, Mu 1 Gene (OPRM1); (rs1799971 A>G; rs540825 T>A) and (III) Catechol-O-Methyl Transferase Gene (COMT); (rs6269 A>G; rs4633 C>T; rs4818 C>G; rs4680 G>A) and the prevalence of chronic pain and disability. iii. Evaluate the gene-gene interaction and association between prioritised SNPs for ABCB1 (rs1045642 G>A; rs1128503 G>A), OPRM1 (rs1799971 A>G; rs540825 T>A) and COMT (rs6269 A>G; rs4633 C>T; rs4818 C>G; rs4680 G>A), and the prevalence of chronic pain and disability in the SA BCS. iv. Conduct bioinformatic analyses to comprehensively examine the functional effects of the prioritised SNPs, identify associated networks and identify potential protein network partners relative to the opioid signalling and pain pathway. Methods A cross-sectional retrospective study was followed (Chapter Error! Reference source not found.), that enrolled two hundred and fifty-two SA BCS. This study was a sub-study of a larger project approved by the Human Research Ethics Committee of the Faculty of Health Sciences within the University of Cape Town (HREC: 312/2012, 125/2017). Qualifying participants were BCS that were diagnosed with unilateral breast cancer ( >1yr before study), older than 18yrs, had no history of neck or shoulder pathology and self-identified as mixed ancestry. Patient-reported pain, disability, and combined symptoms associated with shoulder pathologies were evaluated using the Shoulder Pain and Disability Index (SPADI). Participants scores were calculated and categorized into no-low (A), OPRM1 (rs1799971 A>G), and COMT (rs4680 G>A) . Statistical analysis was performed to describe the relationship between a convenient sample's clinical variables and total drug doses. Moreover, analyses were performed to examine differences in outcome measure scores between the three time points, T1 (pre-operative), T2 ( 3-month post-operative), and T3 (1- year post-operative). Evaluation of the individual genotype, and allele frequencies of each SNPs for each gene between groups were also examined. Haplotype frequencies were statistically inferred for all SNPs within each gene and evaluated between groups. As a proxy for gene-gene interaction, inferred allele–allele combination frequencies were evaluated using the individual genotype data for each SNP. Nonparametric and parametric statistical tests were employed where appropriate, with statistical significance accepted at pA-rs1045642 G>A) haplotype analysis, the inferred G-A (p=0.029, OR: 0.00, 95% CI: 0.00-0.00) haplotype was significantly associated with reduced likelihoods of reporting moderate-high disability. In addition, the inferred A-A (p=0.029, OR:0.63, 95% CI: 0.37-1.06) haplotype was also significantly associated with reduced likelihood of reporting moderate-high combined (pain and disability). The OPRM1 (rs1799971 A>G – rs540825 T>A) inferred G-T (p=0.019, OR:0.33, 95% CI: 0.14-0.75) haplotype was significantly associated with reduced likelihoods of reporting moderate-high pain. Inferred haplotype analysis of five COMT haplotypes noted significant associations for H2-H5, the most notable associations being for the rs6269 A>G -rs4680 G>A genetic interval. This analysis revealed the G-G (p=0.026, OR: 0.67, 95% CI: 0.38-1.18) and A-A (p=0.007, OR: 2.09, 95% CI: 0.89-4.88) haplotypes were associated with reduced and increased likelihood of reporting moderate-high pain, respectively. Gene–gene interaction analyses demonstrated significant associations between the ABCB1 (rs1045642 G>A) – OPRM1 (rs1799971 A>G – rs540825 T>A) and the ABCB1 (rs1045642 G>A) – OPRM1 (rs1799971 A>G). The inferred A-A-T (p=0.029, OR: 0.58, 95% CI: 0.18-1.45) and A-A (p=0.008, OR: 0.44, 95% CI:0.24-0.80) allele-allele combinations were associated with reduced likelihoods of reporting moderated-high combined (pain and disability). ABCB1 (rs1045642 G>A) – OPRM1 (rs540825 T>A) combination analyses demonstrated that the A-T (p=0.019, OR: 0.62, 95% CI: 0.33- 1.16/p=0.014, OR:0.62, 95% CI:0.35-1.10) combination was associated with reduced likelihood of reporting moderate-high disability/combined (pain and disability) symptoms. While the alternate G-A (p=0.021, OR: 1.57, 95% CI: 0.30-3.10/p=0.030, OR: 1.50, 95% CI: 0.78-2.86) combination was associated with increased likelihood of reporting moderate high disability/combined (pain and disability) symptoms. The OPRM1 (rs1799971- rs540825) - COMT (rs4680) combination analyses demonstrated that the A-T-A (p=0.008, OR: 1.36, 95% CI: 0.77-2.41) and G-T-G (p=0.004, OR: 0.00, 95% CI: 0.00-0.00) were associated with increased, and reduced likelihoods of reporting moderate-high pain. Similarly, the OPRM1 (rs1799971 A>G)-COMT (rs4680 G>A) allele-allele combinations A-A (p=0.004, OR: 1.35, 95% CI: 0.85-2.15), and G-G (p=0.010, OR: 0.23, 95% CI: 0.05- 1.03) combinations were associated increased and reduced likelihoods of reporting moderate-high pain and combined (pain and disability). The OPRM1 (rs540825 T>A) - COMT (rs4680 G>A) A-A (p=0.012, OR: 1.89, 95% CI: 0.81-4.38) allele-allele combination was associated increased likelihoods of reporting moderate-high combined (pain and disability). Analyses of the ABCB1 (rs1128503 - rs1045642) - COMT (rs4680) combination demonstrated that the A-A-G (p=0.006, OR:0.68, 95% CI: 0.27-1.71) were significantly associated with reduced likelihood of reporting combined (pain and disability). For the 2-SNP pairing, the ABCB1-COMT (rs4680 G>A) G-A allele combinations were associated with increased likelihoods of reporting moderate-high pain (p=0.005, OR: 2.08, 95% CI: 1.12-3.84), disability (p=0.018, OR: 1.16, 95% CI: 0.62-2.15), and combined (p=0.008, OR: 1.94, 95% CI: 1.02-3.69) groups, pA, and the prevalence of disability, indicating movement-related pain. Despite the absence of an independent association for the functional variant rs1799971 A>G, and rs540825 T>A, for OPRM1, haplotype analyses showed a correlation, supporting the relationship of pain treated with opioids being impacted by this gene. In addition to the independent association observed for COMT rs4680 G>A, gene interactions were observed highlighting the role of collective modulation in pain and disability in the present cohort. Additionally, in-silico analyses revealed strong relationships between the genes and important pathways and mechanisms, further strengthening and supporting the hypotheses presented in the aims of this study. The clinical implications of this study aimed to assist in the understanding of the pain mechanisms and opioid pathways towards the development of novel and innovative therapeutics for pain, in personalized medicine.